Sexually dimorphic gene expression responses of bovine embryos to the maternal microenvironment on day 13 of gestation - Dessie Salilew-Wondim; Ernst Tholen; Christine Große-Brinkhaus; Eva Held-Hoelker; Dennis Miskel; Franca Rings; Karl Schellander; Urban Besenfelder; Vitezslav Havlicek; Dawit Tesfaye; Michael Hoelker (BMC Genomics)
Abstract Background Various studies have highlighted significant differences in developmental kinetics and sensitivity to developmental conditions between male and female bovine embryos. These differences are thought to be caused in part by the sexually dimorphic expression of genes located on the sex or autosomal chromosomes. However, little is known about the dimorphic gene expression patterns of bovine embryos at the initiation of elongation, which is one of the critical stages of development. Furthermore, to the best of our knowledge, there is little or no data available on the sexually dimorphic gene expression patterns in bovine embryos in relation to maternal environmental conditions during the initiation of elongation. Therefore, the main objective of this study was to investigate the sexually dimorphic gene expression responses of embryos to the maternal environment at the initiation of elongation in embryos developed in lactating dairy cows and nonlactating nulliparous heifers. Results Gene expression analysis showed that 159 genes including those involved in steroid biosynthesis and gastrulation were differentially expressed exclusively between male and female embryos developed in cows. Among these, 61 genes including CYP39 A1, CYP2R1 and CYP27B1 were upregulated and 98 genes including HSD17B1, HSD17B10 and aromatase (CYP19 A1) were downregulated in male embryos. Chromosomal analysis showed that 31.2% of the differentially expressed genes (DEGs) including glucose-6-phosphate dehydrogenase (G6PD) were located on the X chromosome, and 96% of those were upregulated in female embryos. Similarly, 254 genes including those involved in female sex differentiation, placenta development, transmembrane transport, and cell adhesion were differentially expressed exclusively between the male and female embryos developed in heifers. Of these, 108 genes including HSD17B11, HSD17B12, and HSD3B1 were upregulated, and 146 genes including SLC16 A9, SLC10 A1, SLC10 A3, SLC16 A5, SLC22 A23, SLC25 A43, SLC35 A2, SLC35 C1, and SLC4 were downregulated in male compared to female embryos. In addition, 17.3% of the DEGs were located on the X chromosome and 75% of the DEGs located on the X chromosome were upregulated in female embryos. On the other hand, 38 genes including SLC30 A10, SLC10 A4, ATP6 AP1, and KDM5 C showed sexually dimorphic expression patterns in day 13 bovine embryos irrespective of the maternal environment. These genes accounted for only 19% and 13% of the genes that showed sexually dimorphic expression in embryos developed in cows and heifers, respectively and the expression difference of these genes in male and female embryos was then likely influenced by the sex of the embryo. Conclusion This study revealed that embryos developed in lactating cows showed sexually dimorphic expression of genes involved in various functions including steroid biosynthesis and gastrulation. In contrast, embryos developed in heifers displayed sexually dimorphic expression of genes related to placental development, female sex differentiation, and transmembrane transport. This suggests that the reproductive tract environments of cows and heifers differently affect the sex specific expression of genes in bovine embryos. A higher proportion of genes that showed sexually dimorphic expression in cow embryos were located on the X chromosome, and the majority of these genes were upregulated in female embryos. Overall, this study provides insight into genes that exhibit sexually dimorphic expression patterns in day 13 bovine embryos due to the maternal reproductive tract microenvironment or solely due to the sex of the embryo.